The Use of Biofiltration Technology and 3-dimensional Cubical Bamboo Shelters for Nursery Phase Productivity Improvement of Giant Freshwater Prawns - Gede Suantika; Pingkan Aditiawati; Malendra Rusni; Rifki R. Arief; Osman R. Turendro (Institute for Research and Community Services (LPPM) ITB, 2012)
This experiment was aimed at finding out the effects of usingnitrifying bacteria and Chlorella sp. and the application of a differing number of 3-dimensional cubical bamboo shelters for enhancing the growth performance of Giant Freshwater Prawns (Macrobrachium rosenbergii de Man) during the nursery phase in an indoor system. During 28 days of culture, treatment II (application of 4 shelters 40% culture volume occupation) resulted in better prawn growth and culture performance compared to control (no shelter application) (p<0,05). At the end of the experiment, treatment II showed the highest biomass, specific growth rate, mean body weight and length of prawns with (1.96+0.05) g.cage-1, 8.24% BW.day-1, (2.18+0,89) g and (6.50+0.91) cm, respectively. However, these results were not significantly different compared to treatment I (application of 2 shelters 20% culture volume occupation). The survival rate after treatment I and II (treatment I=90%, and treatment II=92%) was significantly higher compared to control (78%). During the experiment the increase of the concentration of ammonium and nitrate was controlled by the addition of nitrifying bacteria and microalgae, which can keep the microbial loop between ammonium reduction by bacteria and nitrate uptake by microalgae in balance. The addition of nitrifying bacteria and microalgae, and the availability of 40% bamboo shelter occupation in the culture can improve prawn culture productivity.